Novel strategy for tumor immunotherapy using FITC-folate bispecific adapter bridged CAR immune cell cocktails - Bin Liu; Jingqiao Shen; Yunhan Wu; Chun Fai Wong; Tran Yin Hei; Johnny Wen-tao Li; Sydney N. Hummel; Gyuhyung Jin; Nathan R. Petrucci; Dan Michelle Wang; Xiaoping Bao; Cheng Dong; et al. (Bioactive Materials)
Adoptive immune cell-based therapies have shown promise in cancer treatment, yet their efficacy against solid tumors is often limited by the immunosuppressive tumor microenvironment (TME). To overcome these barriers, we design an innovative immune cell cocktail as a combinatorial biomaterial platform, which harnessing the complementary functions of neutrophils and natural killer (NK) cells derived from human pluripotent stem cells (hPSCs). Using CRISPR/Cas9, we introduce an anti-fluorescein isothiocyanate (FITC) chimeric antigen receptor (CAR) construct into the AAVS1 safe harbor locus of hPSCs, allowing for the differentiation of CAR-modified neutrophils and NK cells. These CAR neutrophils exhibit robust anti-tumor activity, forming immune synapses with tumor cells tagged via a bispecific adapter (FITC-folate), even in hypoxic TMEs, while CAR NK cells demonstrate antigen-specific cytotoxicity. Together, the cocktail biomaterial composed of CAR neutrophils and CAR NK cells creates a synergistic anti-tumor effect: having neutrophils enhance TME modulation, and NK cells provide targeted cytotoxicity. This biomaterial offers a scalable and off-the-shelf solution for producing CAR neutrophils and CAR NK cells, potentially reducing needs for high-dose exogenous cytokines and minimizing immune-related toxicities. Our findings suggest that hPSC-derived CAR neutrophils and CAR NK cells may form an effective immuno-cocktail biomaterial, offering a feasible strategy for advancing solid tumor immunotherapy through cellular synergy and TME adaptation.